Memory and Religious Identity in Ivan IV’s Letters: Constructing Orthodox Kingship in Diplomatic Correspondence - Jovanović, Srđan M. (Occasional papers on religion in Eastern Europe, 2025)
This article examines the use of religious memory and identity in the diplomatic correspondence of Ivan IV (Ivan the Terrible), particularly his letters to the Polish-Lithuanian nobility. Through a detailed analysis of these letters, the article demonstrates how Ivan IV invoked Orthodox Christian imagery, sacred history, and references to past Christian rulers to legitimize his reign and justify his political actions, such as military campaigns and territorial expansion. Ivan’s correspondence not only reflects his self-presentation as a divinely appointed ruler but also illustrates how religious rhetoric played a crucial role in constructing Orthodox kingship and shaping Russian national identity. The study explores the broader implications of religious narratives in statecraft, comparing Ivan IV’s use of religious memory to other Christian rulers. Ultimately, this research contributes to the understanding of the intersection between religion and politics in early modern Eastern Europe and the role of religious identity in shaping autocratic rule.